2004
DOI: 10.1073/pnas.0305877101
|View full text |Cite
|
Sign up to set email alerts
|

Giant plasmid-encoded polyketide synthases produce the macrolide toxin of Mycobacterium ulcerans

Abstract: Mycobacterium ulcerans (MU), an emerging human pathogen harbored by aquatic insects, is the causative agent of Buruli ulcer, a devastating skin disease rife throughout Central and West Africa. Mycolactone, an unusual macrolide with cytotoxic and immunosuppressive properties, is responsible for the massive s.c. tissue destruction seen in Buruli ulcer. Here, we show that MU contains a 174-kb plasmid, pMUM001, bearing a cluster of genes encoding giant polyketide synthases (PKSs), and polyketide-modifying enzymes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
344
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 347 publications
(353 citation statements)
references
References 27 publications
3
344
0
4
Order By: Relevance
“…Initial MLSA analyses and subsequent whole-genome comparisons have shown that M. ulcerans has recently evolved from M. marinum by acquisition of the pMUM plasmid and reductive evolution (31)(32)(33)(34). The recent discovery of MPM that are phenotypically distinct from M. ulcerans in diseased fish and frogs has highlighted the possibility that pMUM is being transferred among different mycobacterial species (19,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial MLSA analyses and subsequent whole-genome comparisons have shown that M. ulcerans has recently evolved from M. marinum by acquisition of the pMUM plasmid and reductive evolution (31)(32)(33)(34). The recent discovery of MPM that are phenotypically distinct from M. ulcerans in diseased fish and frogs has highlighted the possibility that pMUM is being transferred among different mycobacterial species (19,26).…”
Section: Discussionmentioning
confidence: 99%
“…However, other than travelers returning from countries where the disease is endemic, no cases of BU have ever been reported in the United States or Europe. M. ulcerans strains are characterized by the presence of a large circular virulence plasmid called pMUM (31,33). This plasmid harbors three large genes (mlsA1, mlsA2, and mlsB) encoding polyketide synthases that are required for the synthesis of the lipid toxin mycolactone, which is the primary virulence factor for the pathogen (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…pMUM001 also has three accessory genes that are involved, or have a predicted role, in mycolactone synthesis. These genes include mup038, encoding a putative type II thioesterase, mup045, encoding a potential acyltransferase that might catalyse the C-O bond between the mycolactone core and side-chain, and mup053 (cyp140A7), encoding a P450 monooxygenase that hydroxlates C129 of the side-chain (Stinear et al, 2004(Stinear et al, , 2005a. The mlsA1, mlsA2 and mlsB genes span 105 kb and encode 11 different functional domains that are repeated across the two load modules (LMs) and 16 extension modules that comprise these PKS.…”
Section: Introductionmentioning
confidence: 99%
“…The major virulence factor in M. ulcerans is a necrotizing toxin called mycolactone, a macrolide consisting of a polyketide side chain attached to a 12-membered core encoded by genes harboured in a large 174-kb plasmid [7]. This toxin has cytotoxic, analgesic and immunosuppressive activities [8][9][10].…”
Section: Introductionmentioning
confidence: 99%